Sustainable Marketing Strategies And The Influence Of Environmental Factors On Consumer Purchase Intention: The Role Of Environmental Awareness Intervention (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the dynamic landscape of contemporary business, the adoption of sustainable marketing practices is imperative for companies seeking to harmonize economic goals with environmental responsibility. This research investigates the interplay between sustainable marketing strategies, environmental factors, and consumer behavior within the operational framework of PT AKR Corporindo Tbk in Medan. The study explores direct and indirect relationships to discern the impact of marketing strategies and environmental factors on both consumer awareness and purchasing decisions. While marketing strategies significantly influence consumer purchases, the role of environmental factors in shaping consumer behavior is more nuanced. The study emphasizes the importance of aligning marketing initiatives with consumer values and recognizing the mediating role of environmental awareness in influencing purchasing decisions. These findings contribute valuable insights for businesses operating in logistics, energy distribution, and trading, offering a comprehensive understanding of the complex dynamics at the intersection of sustainable practices and consumer preferences.
Keywords: Marketing Strategies, Environmental Factors, Consumer Purchase, Environmental Awareness